A retrospective assessment of mortality from the London smog episode of 1952: the role of influenza and pollution. - Bell, Michelle L (2004)
The London smog of 1952 is one of history's most important air pollution episodes in terms of its impact on science, public perception of air pollution, and government regulation. The association between health and air pollution during the episode was evident as a strong rise in air pollution levels was immediately followed by sharp increases in mortality and morbidity. However, mortality in the months after the smog was also elevated above normal levels. An initial government report proposed the hypothesis that influenza was responsible for high mortality during these months. Estimates of the number of influenza deaths were generated using multiple methods, indicating that only a fraction of the deaths in the months after the smog could be attributable to influenza. Sensitivity analysis reveals that only an extremely severe influenza epidemic could account for the majority of the excess deaths for this time period. Such an epidemic would be on the order of twice the case-fatality rate and quadruple the incidence observed in a general medical practice during the winter of 1953. These results underscore the need for diligence regarding extremely high air pollution that still exists in many parts of the world.